Association of traditional Chinese medicine (tcm) body constitution, fasting blood glucose and waist circumference with capn10 (rs2975760) and hnf1a (rs735396) - Tan, Shu Rou (2024)
Metabolic syndrome (MetS) is a condition characterized by elevated blood glucose levels and increased waist circumferences, leading to type 2 diabetes mellitus (T2DM) and abdominal obesity. Traditional Chinese Medicine (TCM) categorizes individuals into different body constitutions, offering insights into disease prevention and diagnosis. Genetic variations such as single nucleotide polymorphisms (SNPs) in Calpain-10 (CAPN10) and Hepatocyte Nuclear Factor 1 Alpha (HNF1A) genes have been implicated in T2DM pathogenesis. This study contributes to a deeper understanding of the complex interplay between genetic variants, metabolic health and TCM body constitutions. A total of 80 eligible subjects were recruited and demographic factors (gender, age and ethnicity) were considered. Interview-based TCM body constitution assessment was conducted, venous blood samples were collected for DNA analysis (genotyping) and fasting blood glucose (FBG) levels and waist circumference were measured. IBM SPSS Statistical 26.0 was used for data analysis. This study found 1.25% and 24.20% prevalence of diabetes and abdominal obesity, respectively. Minor allelic frequency (MAF) for rs2975760 and rs735396 were greater than 0.05, indicating their significance in the study population. A weak positive correlation was found between FBG levels and waist circumference, reflecting the impact of abdominal obesity on T2DM. Gender-based differences in FBG levels and waist circumferences were observed, possibly due to hormonal influences. FBG levels and waist circumferences differed significantly across five age groups, while no significant differences in FBG levels among ethnicities. There was no significant association between TCM body constitutions and genetic variations, suggesting the challenge of assessing dynamic nature of body constitutions. Rs2975760 (CAPN10) showed no significant differences in relation to FBG levels and waist circumference. The mutant CC allele of rs735396 (HNF1A) was associated with significantly lower FBG levels, but not for waist circumference. Further research involving larger and more diverse samples is recommended to fully understand the interactions between these variables.